IMPLEMENTASI RESTORATIVE JUSTICE PADA PENEGAKAN HUKUM TINDAK PIDANA PENCABULAN OLEH ANAK DI WILAYAH HUKUM DIREKTORAT RESERSE KRIMINAL UMUM KEPOLISIAN DAERAH RIAU - Kurniawan, Singgih Warsito; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Crime is a fact of life that requires special handling. Crime is increasing in Indonesia resulted in the incidence of a variety of modus operandi in the crimes, one form of evil acts of violation of minors. From the results of the research problem, there are three basic things that can be summed up: the first application of Restorative Justice in the Directorate of Police of Riau Area became Reserse options various parties (victim/offender/family, family and investigators) with consideration for the application of the concept of restorative justice is more fulfilling sense of fairness for both parties. But not all cases are resolved in the case of Restorative Jutice let alone already berualang times performed and led to heavy losses. Second, barriers in Imlementasi Restotive Justice that provisions of legislation that has not been set explicitly the application of Restorative Justice concepts of Justice as an alternative to the completion of the legal apparatus of making children matter has no clear juridical footing to resolve the matter through the concept of Restorative Justice. Third, Efforts are being made to overcome the obstacles in the implementation of Restorative Justice in the Riau regional police Direserse where investigators provide referrals and understanding to the families of the victims nor the perpetrators for as much as possible eliminate the sense of revenge tarhadap crime and give an understanding that any process of criminal acts committed by children under the age of restorative justice were resolved or peace.